Characterization of alginate from Antarctic Himantothallus grandifolius (Phaeophyceae) and preparation of polyelectrolyte complexes with chitosan - Candia, Carolina; Gallardo-Moya, Daniel; Guerrero, Juan; Leal, David; Mansilla Muñoz, Andres Omar; Martinez-Gomez, Fabian; Matsuhiro, Betty; Yanez-S, Mauricio (My University, 2023)
Hydrogels are three-dimensional polymeric materials with applications in various areas such as biomedicine, tissue engineering, pollutant capture systems, and so forth. However, its application is limited due to the reproducibility of its properties. Factors such as the composition of the constituents, the type of union between the polymer chains, and the crosslinking time play a crucial role in ensuring its reproducibility. In this study, the objective is to prepare a matrix with well-defined properties that ensure controlled release processes. Treatment of Himantothallus grandifolius with Na2CO3 aqueous solution afforded in 18.9% yield alkaline extract. Hydrogels were prepared by ionic complexation of alginate from H. grandifolius, and polyguluronate enriched alginate from Desmarestia ligulata with chitosan stabilized by immersion in 0.1 M CaCl2 solution; better swelling ratio in water was found for hydrogels with low molecular weight chitosan (MW 125,000 g/mol) than those with medium molecular weight chitosan (MW450,000-500,000 g/mol). Liberation of the model drug metformin hydrochloride from alginates: chitosan complexes (3:1) at pH 1.5 was especially low for hydrogel from H. grandifolius during the first 2 h; 70% of metformin was released at pH 6.5 after 24 h. This polyelectrolyte complex constitutes a good material for potential application in biomedicine considering its cationic and anionic characteristics.
Keywords: alginate; chitosan; drug release; himantothallus grandifolius; hydrogels; polyelectrolyte complexes